Gender Equality in Schools: Providing Gender Equality Learning Environment - Pebrina Nurwahyuningsih; Nurianti Nurianti; Nurlinda Nurlinda (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Gender equality implementation in education aspect in Indonesia is still far from the ideal criteria. One of the reasons is affected by the patriarchal culture that constructs society’s perspective. The Indonesian government has conducted many studies on gender to promote gender equity and inclusion in Indonesia. As a result, the Minister of Education issued regulation No.84/2008 concerning guidelines for the implementation of gender in education. However, access to education, quality education, and the level of participation of women still lack (Lestariyana, et al., 2020; Lestyoningsih, 2020; Mustofa, et al., 2021; Natasha, 2013; Suwarno, et al., 2021; Tyarakanita, et al., 2021). Thus, it is necessary to conduct a comprehensive literature review to illustrate the implementation of gender equality in schools to promote awareness. Through qualitative descriptive study, a variety of publications and journal articles were analyzed. The literature review was divided into three sections, involving the portrayal of gender equality in Indonesia, gender bias in education, and implementation of gender equality in school. The study concludes some aspects that should be implemented to create a gender-responsive school environment and raise the awareness of the students, including the development of curriculum, learning methods, teacher development, and continuous assessment. Developing all these aspects periodically means breaking down the “traditional” cultural concept of gender, which certain genders sometimes excluded. Development needs to be done to ensure the school promotes and facilitates gender equality.